Pengaruh Latihan Box Shuffle Step Dengan Double Box Shuffle Step Terhadap Power Tungkai - Nurfaidah, Vina; Risma, Risma; Nursasih, Isna Daniyati; Erlina, Terra (Universitas Galuh, 2024)
Increasing the explosive power movement performance of both leg muscles is the aim of training with two independent variables, namely box shuffle step and double box shuffle step. This study was implemented namely pre-experiment. The research design used was a two group pretest-posttest design. The research location is the Itsbatul Husna Panumbangan Pencak Silat College, Ciamis Regency. The subjects included consisted of 10 boys and 10 girls. Each group has 5 male participants and 5 female participants. So it consists of two groups. The measuring tool used is jumping straight up. The statistical process uses SPSS 25. The results of the study are: 1. There is a positive influence for the box shuffle step on changes in leg power in students at Itsbatul Husna Panumbangan Pencak Silat College, Ciamis Regency. 2. There is a positive influence for the double box shuffle step on changes in leg power in students at Itsbatul Husna Panumbangan Pencak Silat College, Ciamis Regency. 3. There is no difference between the box shuffle step group and the double box shuffle step group for changes in leg power in students at Itsbatul Husna Panumbangan Pencak Silat College, Ciamis Regency. Conclusion: Box shuffle step training with double box shuffle steps to change leg power in students at Itsbatul Husna Panumbangan Pencak Silat College, Ciamis Regency. Suggestion: Box shuffle step training with double box shuffle steps can be used as an alternative leg power exercise.Penambahan performa pergerakan daya ledak ke-dua otot tungkai sebagai tujuan dari latihan dua variabel bebas yaitu box shuffle step dengan double box shuffle step. Studi ini diterapkan yaitu pre-eksperimen. Desain penelitian yang dipakai yaitu two group pretest-postest design. Tempat penelitian yaitu di Perguruan Pencak Silat Itsbatul Husna Panumbangan Kabupaten Ciamis. Subjek yang diikutsertakan terdiri dari 10 orang putra dan 10 orang putri. Setiap kelompok memiliki peserta laki-laki 5 orang dan perempuan 5 orang. Sehingga terdiri dari dua kelompok. Alat ukur yang dipakai yaitu loncat tegak ke atas. Proses statistik memakai SPSS 25. Hasil studi yaitu: 1. Adanya pengaruh yang positif untuk box shuffle step untuk perubahan power tungkai pada siswa Perguruan Pencak Silat Itsbatul Husna Panumbangan Kabupaten Ciamis. 2. Adanya pengaruh yang positif untuk double box shuffle step untuk perubahan power tungkai pada siswa Perguruan Pencak Silat Itsbatul Husna Panumbangan Kabupaten Ciamis. 3. Tidak ada perbedaan antara kelompok box shuffle step dengan double box shuffle step untuk perubahan power tungkai pada siswa Perguruan Pencak Silat Itsbatul Husna Panumbangan Kabupaten Ciamis. Kesimpulan: Latihan box shuffle step dengan double box shuffle step untuk perubahan power tungkai pada siswa Perguruan Pencak Silat Itsbatul Husna Panumbangan Kabupaten Ciamis. Saran: Latihan box shuffle step dengan double box shuffle step dapat dijadikan alternatif latihan power tungkai.